Validating the language mindset inventory in Finland: a study of higher education students’ language-learning mindsets - Matthew Billington; Sonja Laine; Kirsi Tirri (Frontiers in Psychology)
IntroductionIn recent years, mindset research has increasingly focused on domains of learning, such as mathematics. Foreign/second language (L2) learning is a recent addition to the domain-specific mindset literature. However, few studies have focused on language mindsets in a European context. Moreover, the Language Mindsets Inventory (LMI), the instrument commonly used to measure such mindsets, has not been validated outside North America and Asia.MethodsTo address this gap, the LMI was administered to over 300 students taking compulsory L2 courses at a university in Southern Finland. The construct validity of the LMI was assessed using confirmatory factor analysis (CFA) and hierarchical factor analysis (HFA). The study then used the LMI data to assess the orientation of the students’ language mindsets (fixed or growth) and their correlation with beliefs about general intelligence and giftedness.ResultsThe results indicated that the LMI’s three subscales—general language beliefs, L2 beliefs, and age-sensitive beliefs—represent distinct constructs, in turn stratified by growth-mindset (incremental) and fixed-mindset (entity) beliefs. The students’ language mindsets measured by all six resultant factors were more growth oriented than their mindsets about general intelligence and giftedness. In addition, the students’ language mindsets were more growth oriented as measured by the incremental items of the LMI than by the entity (fixed) items.DiscussionThe results suggest that the LMI is a valid instrument for use in Finnish higher education contexts. However, the data do not support combining the scores from the subscales, as the constructs they measure are too distinct. In general, more research is required on why entity and incremental mindset items in mindset scales produce different results about the strength of respondents’ mindset orientations.